The Issue of Dramaturgy in Youth Education and Puppet Theater - Sayidolim, Khojaev; A’zamjon, Abdukhalilov (Research Parks Publishing LLC, 2023)
This article talks about the puppet theater, which is a unique type of theatrical art, and important aspects of its dramaturgy.